2016
DOI: 10.7759/cureus.702
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Monitoring of Prostatic Lesions: A Comparison of Three Modalities: Multiparametric MRI, Fusion MRI/Transrectal Ultrasound (TRUS), and Traditional TRUS

Abstract: Purpose: Transrectal ultrasound (TRUS) has been the gold standard of imaging for diagnosing prostate cancer for decades but is plagued by user error and undersampling. We aim to explore imaging modalities that are now being used in combination or alone for screening, diagnosis, and/or active surveillance of prostate cancer.Methods: A PubMed literature search was performed to include articles published up to April 2016. Data were extracted and analyzed.Results: Several large-scale studies have found an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The gold standard for the diagnosis of prostate cancer was an ultrasound-guided biopsy. Birs A (24) and other studies had shown that the MRI-TRUS fusion technique has a very high biopsy rate for PCa. However, fusion biopsies required a longer learning curve (25,26).…”
Section: Discussionmentioning
confidence: 95%
“…The gold standard for the diagnosis of prostate cancer was an ultrasound-guided biopsy. Birs A (24) and other studies had shown that the MRI-TRUS fusion technique has a very high biopsy rate for PCa. However, fusion biopsies required a longer learning curve (25,26).…”
Section: Discussionmentioning
confidence: 95%
“…To increase the detection rate for patients to plan a repeat biopsy, several strategies including extended biopsies, targeted biopsy of mpMRI-suspicious areas, and transperineal saturation biopsies, were suggested. 18 , 19 mpMRI is recommended in men who are candidates for repeat biopsy, the detection rate for PCa is between 39% and 59%, and the incidence of cancer located only in the anterior zone is 20%. 20 , 21 , 22 Although various biopsies protocol before repeat prostate biopsy showed higher detection rate than standard transrectal ultrasound (TRUS)-biopsy, mpMRI is not reimbursed for patients suspected with PCa in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we previously reported that the inclusion of prostate volume as an additional variable with FLNA provided superior predictive power for diagnostics. Prostate volume is quantified via transrectal ultrasound (TRUS); however, TRUS can pose some challenges regarding obtaining accurate volumetric measurements due to human error and is found to be highly user-dependent [6,7]. Additionally, TRUS exposes patients to unnecessary procedures that might result in complications [8,9].…”
Section: Introductionmentioning
confidence: 99%